The hidden curriculum and its marginalisation of Longitudinal Integrated Clerkships. Issue 6 (1st November 2020) - Brown, Megan E. L.; Hafferty, Frederic W.; Finn, Gabrielle M.
ABSTRACT: Longitudinal Integrated Clerkships (LICs) have a growing presence as a model of educational delivery on the stage of UK medical education, where they are most frequently based within primary care. Yet, despite both local and internationally reported benefits, significant challenges to programme implementation and student engagement remain. Although perhaps initially challenges could be explained by the novelty of LICs, UK LICs have aged, yet challenges remain, leading to the marginalisation of LICs within UK medical schools. This leading article suggests institutional hidden curricula may be an important vehicle for this marginalisation and explores how the dominant fact-based paradigm of UK medical education could act to dissuade student engagement with LICs. So long as the hidden curricula messages we transmit to early-stage medical students revolve around the disproportionate importance of cognitive knowledge acquisition, UK-based LICs are unlikely to realise their full impact or benefit, in comparison to successfully running LICs internationally. Alternatively, refocusing early medical education on patient interaction, encouraging students to take an active role in their care, would send a different hidden curricula message more aligned with the ethos of LICs, and so would likely increase uptake to later stage comprehensive programmes.